Impact of Emotional Self-Regulation and Stress Management on Socioemotional Wellbeing: A Study in Secondary School Students - Torres Gamez, Nicolas Alejandro; Galleguillos, Marcelo Chavez; Sanchez, Misael Silas Letelier (Journal of Posthumanism, 2025)
Background: Emotions self-regulation is an important field of study in psychology today since it helps people take better decision in their daily life. In the context of education, an emotional self-regulation will help students reach a positive learning environment in their development in society and as students This study focuses on emotional management through the analysis of the abilities to recognize and express emotions. The study aims to explore the relation between emotional self-regulation and socioemotional wellbeing in secondary education students. Methods: A non-experimental design was carried out with a cross-sectional modality in August 2024. It has a quantitative, exploratory, and descriptive approach seeking to describe the phenomenon in its context. The instrument applied was the BarOn EQI Questionnaire (Emotional Quotient Inventory) to measure emotional intelligence in adolescents and adults and evaluate five principal sub-components with subscales. Results: The study found positive correlations between emotional wellbeing dimensions, including the intrapersonal component (CIA) and stress management (CME), with the latter being a key predictive variable. Conclusions: According to the results, the need to implement pedagogical strategies for developing socioemotional skills in students is imperative, considering aspects as the institutional context and gender differences. In the same vein, it is necessary to strengthening stress management in both genders, adapted to the characteristics of each group for a better socioemotional wellbeing. Future research should aim at including longitudinal focus and qualitative data to enrich the comprehension of emotional dynamics in school contexts, exploring this topic in different cultural environments under local educational policies.